Consequence Modelling of Biogas Release from Storage Tanks Using EFFECTS Software - Nashira, Alimatun; Afrilia, Heningtyas Dwi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Biogas is a renewable energy source with the potential to reduce dependence on fossil fuels and greenhouse gas emissions. However, handling biogas requires special attention to safety and security aspects due to its flammable and toxic nature. This study aims to model the consequence of biogas release using the EFFECTS software. The simulation varies pressure levels (1034, 1500, 2000, 2500, 3000 mbar), biogas composition, and atmospheric conditions (Pasquill stability classes B, C, and F). The modelling analyses the potential consequences of a biogas release incident, taking into account meteorological and topographical conditions that influence gas dispersion. The worst impacts of explosion and toxic gas dispersion occur under stable atmospheric conditions (Pasquill stability class F). Storage tank pressure has little effect on the overpressure contour distance, with the light damage zone only reaching a maximum distance of 68 meters from the tank. However, biogas tank pressure significantly affects the reach of toxic substances, where a leak from a tank at 3000 mbar results in AEGL-2 and AEGL-3 zones extending up to 7086 meters and 2779 meters, respectively. Biogas compositions with higher methane content have a slightly larger explosion range, while those richer in carbon dioxide have a farther reach of toxic substances, though the differences are not significant. The results of this simulation are expected to provide valuable insights for industrial accident prevention efforts and the enhancement of safety standards in the renewable energy sector, particularly in biogas management.